The Jaws book new perspectives on the classic summer blockbuster - Hunter, I. Q. 1964-; Melia, Matthew; Gottlieb, Carl 1938- (Bloomsbury Academic, Bloomsbury Publishing Inc, 2020)
"A collection offering new research and insights into Steven Spielberg's classic thriller Jaws"--